Pelatihan Tugas Perawatan Kesehatan Keluarga Caregiver Lansia dalam Pogram RURAL (Rumah Ramah Lansia) - Annisa Wuri Kartika; Muladefi Choiriyah; Niko Dima Kristianingrum; Linda Wieke Noviyanti; Endah Panca Lidya Fatma (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
The decline in function due to aging accompanied by health problems in the elderly has an impact on the ability of the elderly in activity daily living (ADL) and health care. The role of the family is very important in health care assistance to the elderly. Caregiver skills accompanied by environmental aspect are important factors for elderly with chronic illness at home. This community service aims to improve the caregiver's ability to provide care to the elderly with chronic illness. RURAL (Rumah Ramah Lansia) is activity to create a suitable environment for the elderly in terms of physical and psychosocial environment. The families trained as a caregivers which are carried out in RW 4, Jatimulyo, Malang City in January - March 2018. The activities of the program is health education and skill training about caring for elderly. The results are 70 percent of families have good ability in carrying out family health care tasks; knowledge about elderly care at home is good with an average knowledge value of 8.6. From these results it can be concluded that training for caregivers is useful to improve the ability of caregivers and health status of the elderly.Keywords: caregiver care ability; chronic disease; elderly care at home.